Thermodynamic models for chemical engineering - Jaubert, Jean-Noel; Privat, Romain (Elsevier, 2019)
Thermodynamic Models for Chemical Engineering gives an overview of the main thermodynamic models used by engineers and in engineering researcher processes. These fall into two main families, equations of state and activity coefficient models. The book presents the state-of-the-art of purely predictive models.